Implementation of Religious Moderation at SDN Karangasih 13, Cikarang Utara, Bekasi - Siti Ropiah; Coan Alfian (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to analyze the implementation of religious moderation at SDN Karangasih 13, Cikarang Utara, Bekasi. Religious moderation refers to a balanced approach that promotes tolerance, respect for diversity, and rejection of extremism in practicing religious life. Implementing religious moderation in elementary schools plays a strategic role in shaping students' character from an early age to live harmoniously in diversity. This research uses a qualitative descriptive approach with data collection methods including observation, interviews, and documentation. The subjects of the study include teachers, students, the principal, and educational staff at SDN Karangasih 13. The results show that the implementation of religious moderation in the school is carried out through three main aspects: (1) Integration of religious moderation values into the curriculum, particularly in Religion and Pancasila Education subjects; (2) School activities that promote tolerance and inclusivity, such as joint celebrations of religious holidays; and (3) Instilling moderation values through school culture, such as mutual cooperation, respect for others, and dialogue among school members. However, challenges remain, such as differing understandings of religious moderation among parents and limitations in providing learning resources that support these efforts. In conclusion, the implementation of religious moderation at SDN Karangasih 13 has been well-executed through a holistic approach involving the curriculum, school culture, and extracurricular activities. Nevertheless, strengthening collaboration with external parties is needed to achieve more optimal outcomes.